Algorithms for biomedical image reconstruction and rendering - Foo, Dillion Jia Yew. (2010)
The goal of segmentation is to simplify and/or change the representation of an image into something that is more meaningful and easier to analyze. This report details the project taken by the author which shows how the Insight Development ToolKit (ITK) can be used to develop biomedical images from radiography for image analysis.